Three new species of Collembola from soils of Mediterranean cork-oak forests of Sicily (Italy) - Giuga, Luca; Jordana, Rafael (Zootaxa, 2013)
Three new species of soil Collembola from cork-oak (Quercus suber) forests located in eastern Sicily (Italy) are described: Neonaphorura alicatai sp. nov., Friesea guarinoi sp. nov. and Arrhopalites antonioi sp. nov..